The pillow police campaign - Agustin Joan Marie Lavalle (2015)
This paper presents The Pillow Police, a public information campaign about child sleep deprivation, initiated by four final year students from the Wee Kim Wee School of Communication and Information, Nanyang Technological University. The campaign aimed to educate parents of primary school children aged six to nine on improving their child’s sleep hygiene. The paper summarises primary and secondary research that shaped the campaign’s messaging, strategies and tactics. Aside from studying present literature, a survey study was also conducted. The focus of the survey was on the sleep habits of children, parents’ perception of their child’s sleep, and parents’ level of awareness of sleep deprivation. From the research conducted, the campaign’s key messages and Let’s Free Our Zees: The Pillow Police Toolkit were designed to educate parents on knowledge about sleep deprivation and tips to help their child sleep better. Campaign outreach activities were developed to bring forth the key messages of the campaign through community engagement. Online platforms were used in tandem with offline outreach platforms, to expand reach to target audience. The paper concludes with an evaluation of the campaign through a post-campaign survey, metrics from campaign activities, analysis of media coverage and appraisals from stakeholders. Future opportunities for continuation of the campaign through possible adaptations by various health boards and societies are also highlighted. Campaign collaterals, photos of the campaign’s outreach activities, as well as tables, and lists detailing the campaign’s execution, can be found in the appendices.